European Voices III The Instrumentation and Instrumentalization of Sound Local Multipart Music Practices in Europe - Ahmedaja, Ardian (Böhlau, 2017)
Local multipart music practices are based on the intentionally distinct and coordinated participation of music makers in the performing act. Following the rules of interaction while promoting at the same time their personal goals, the protagonists share their own treasure trove of experiences and cultural affiliations and shape sounds and values. Such complex and dynamic processes are central to the investigations of instrumentation and instrumentalization of sound. DVD: http://e-book.fwf.ac.at/o:1078